Experimental Study of the Effect of Slope on the Spread and Burning Characteristics of a Continuous Oil Spill Fire - Xiaoxiao Sun; Hong Huang; Jinlong Zhao; Guangheng Song (Fire, 2022)
Elucidating the characteristics of continuous oil spill fires for different slope conditions can provide important theoretical support for the prevention of, and rescue strategies during, oil spill fire accidents. For this research, we conducted experiments to observe the spread and burning process of continuous oil spill fires under different slope conditions. The changes in physical attributes, such as flame spread rate, burning rate, heat convection at the bottom surface, and flame feedback radiation, were analyzed for the different slope conditions. The results showed that the shrinking phase becomes difficult to see, and the steady phase disappears when the slope increases in the spread and burning process. When the slope increases, the spread speed and spread area increase, and burning rate decreases. Compared with a non-burning process, the resistance to spread decreases in the burning process. We show that the slope directly affects the spreading process, and indirectly affects the burning process.